2018
DOI: 10.12659/msm.909669
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Androgen Receptor Variant 7 (AR-V7) in Circulated Tumor Cells and Correlation with Drug Resistance of Prostate Cancer Cells

Abstract: BackgroundProstate cancer is a common type of malignant tumor invading the male reproductive-urinary system, which has increasing incidence worldwide. Androgen receptor variant 7 (AR-V7) participates in regulating prostate cancer cell proliferation and gene expression. This study aimed to investigate the expression of AR-V7 in circulated tumor cells (CTCs) in patients with prostate cancer and to assess its correlation with drug sensitivity against enzalutamide or abiraterone.Material/MethodsBlood samples of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…1D ). Enhanced levels of AR-V7 are associated with increased drug resistance 6 , 27 .
Figure 1 Expression of AR-FL and AR-V7 in an isogenic model of enzalutamide resistance.
…”
Section: Resultsmentioning
confidence: 99%
“…1D ). Enhanced levels of AR-V7 are associated with increased drug resistance 6 , 27 .
Figure 1 Expression of AR-FL and AR-V7 in an isogenic model of enzalutamide resistance.
…”
Section: Resultsmentioning
confidence: 99%
“…For instance, AR-V7 (also termed AR3) and AR-V3 have been described as constitutively active and are recurrently expressed in CRPC [ 129 , 130 , 136 , 138 , 139 ]. Furthermore, AR-V7 has been strongly associated with ARSI resistance (e.g., enzalutamide and abiraterone acetate), tumor growth, and poor patient prognosis [ 133 , 135 , 140 , 141 ]. Consequently, AR splice variants are central players in CRPC.…”
Section: Ecm Stiffness and Mechanisms Promoting Resistance To Ar-targ...mentioning
confidence: 99%
“…Using qualitative RT-PCR, Wang et al found that the expression of androgen receptor variant 7 (AR-V7) in CTCs from patients with prostate cancer was associated with drug resistance. e upregulation of AR-V7 led to the enhancement of cancer cell proliferation, suggesting poor patient prognosis [114]. Wei et al recruited 78 patients with stage I A2 -II A1 cervical cancer who had undergone radical hysterectomy by laparotomy or laparoscopy and selected 34 uterine fibroid patients and 32 healthy subjects as the positive control group and negative control group, respectively.…”
Section: Rt-pcrmentioning
confidence: 99%